COMPARATIVE EFFECTS OF SCREW PRESS FOR HONEY EXTRACTION FOR SMALL SCALE HONEY PROCESSING (Nigerian Journal of Technology, 2013)
Honey extraction is the removal of honey from the honey bearing combs. Different local methods of honey extraction, their strengths and weaknesses were discussed. A screw press was fabricated to facilitate honey extraction. The fabricated screw honey extractor is good alternative to the existing methods of extraction. The extractor ensures timeliness, reduces drudgery involved in the extraction. Similarly, risk of contamination, overheating, overexposure to the environment, contact with hands and the filtering medium are bound to be reduced. It is affordable, durable and requires no special skill to be operated. It has an output capacity of 42.48kg/hr. The cost of fabricating the machine is N29, 000.00 only. It is highly recommended for both small and medium scale honey processors. Design related engineering properties of honeycomb should also be determined. Finally, containers and processing equipments such as stainless steel and other related food grade plastics compatible with acidic food should used for the construction.